DARI BATU PANGGAL KE SUMUR MATHILDA: WARISAN ENERGI SEBAGAI IDENTITAS SOSIAL KALIMANTAN TIMUR - Reza Mahendra Juniar (Lambung Mangkurat University, 2026)
This conceptual article examines the historical and social dynamics of energy development in East Kalimantan, Indonesia, by tracing the transformation from coal mining in Batu Panggal to oil exploration at the Mathilda Well in Balikpapan. The region’s industrial history illustrates how colonial economic expansion shaped local social structures, urban growth, and collective identity. The main problem addressed in this study is the lack of reinterpretation of these industrial remnants as part of Indonesia’s cultural and educational heritage. The objective of this paper is to propose a conceptual framework that repositions industrial sites not merely as colonial relics but as valuable industrial heritage assets that embody the community’s historical consciousness and socio-cultural identity.This study employs a library research method by reviewing historical documents, academic literature, and recent theoretical works related to industrial heritage and energy colonialism. The discussion emphasizes the synthesis between these two frameworks to construct a new understanding of energy history as a cultural process. The findings suggest that the legacy of energy industries in East Kalimantan, represented by Batu Panggal and the Mathilda Well, can serve as a foundation for history education, cultural preservation, and community-based heritage tourism. Reinterpreting energy heritage in this way fosters critical historical awareness and strengthens local identity as an integral part of Indonesia’s national history.